PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERPENDEKATAN PBL TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR - Hasan Albana Rhomadhon; Joko Waluyo; Slamet Hariyadi (Saintifika, 2016)
Abstract: Critical thinking skills are included in high-level thinking skills that train students to think logically, scientifically, and are relevant in solving problems. These skills need to be applied in the learning of the modern era today, one of which is PBL-based TPS learning that has the thinking syntax of thinking, grouping, and sharing opinions, combined with a problem-based approach. This study aims to determine the effect of Think Pair Share (TPS) learning models based on the Problem Based Learning (PBL) approach to critical thinking skills and students' biology learning outcomes. The population in this study were students of class XI MIPA at Balung Jember High School in the academic year 2017/2018. The research sample was class XI MIPA 2 as the experimental class and class XI MIPA 1 as the control class. The results showed that the Think Pair Share learning model based on the Problem Based Learning approach had a significant effect on critical thinking skills with a significance of (p = 0,000) and was also able to improve students' biology learning outcomes in the cognitive, affective and psychomotor domains. Keywords: critical thinking skills; Think Pair Share; problem-based approach.